Can I keep him? - Kellogg, Steven (New York : Dial, 1991)
Mother objects to every pet Arnold asks to keep except one--a person.
4.4
K-3
K-3
Wilson's Children
School Library Journal
Library Journal
Keywords: Pets -- Fiction; Pets -- Fiction